2021
DOI: 10.1007/s42979-020-00416-4
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Requirements Elicitation: A Systematic Literature Review

Abstract: Requirements engineering has traditionally been stakeholder-driven. In addition to domain knowledge, widespread digitalization has led to the generation of vast amounts of data (Big Data) from heterogeneous digital sources such as the Internet of Things (IoT), mobile devices, and social networks. The digital transformation has spawned new opportunities to consider such data as potentially valuable sources of requirements, although they are not intentionally created for requirements elicitation. A challenge to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 101 publications
0
29
0
2
Order By: Relevance
“…In recent years, scholars have been also studying on-line user feedback from other digital sources such as microblogs e.g., Twitter (Guzman et al 2017), on-line forums e.g., Reddit (Khan et al 2019), or issue tracking systems e.g., JIRA (Nyamawe et al 2019). Most research efforts, however, have been focused on analyzing app reviews (Lim et al 2021). Supposedly, the large number of this data, their availability and their usefulness make app reviews unique and thus the most frequently studied type of on-line user feedback (Lim et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, scholars have been also studying on-line user feedback from other digital sources such as microblogs e.g., Twitter (Guzman et al 2017), on-line forums e.g., Reddit (Khan et al 2019), or issue tracking systems e.g., JIRA (Nyamawe et al 2019). Most research efforts, however, have been focused on analyzing app reviews (Lim et al 2021). Supposedly, the large number of this data, their availability and their usefulness make app reviews unique and thus the most frequently studied type of on-line user feedback (Lim et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Most research efforts, however, have been focused on analyzing app reviews (Lim et al 2021). Supposedly, the large number of this data, their availability and their usefulness make app reviews unique and thus the most frequently studied type of on-line user feedback (Lim et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…SWOT analysis can facilitate software requirements as well [34,35]. Recently, eliciting requirements from online user reviews has become a software engineering trend [36,37]. With the help of NLP, Groen et al [38] found that the automatic analysis of user requirements has better scalability than manual analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that manufacturers can make use of online review data to make favorable decisions and gain competitive advantages [12,13]. And there are plenty of studies applying nature language techniques or machine learning techniques to mining user requirements from online reviews, such as review cleaning, information extraction, and sentiment analysis [14].…”
Section: Theoretical Frameworkmentioning
confidence: 99%